Digital citizenship: Challenges and uncertainty in applying blockchain - Ramírez López, Leonardo Juan; Parra Chavarro, Danniel Alejandro; Hernandez Huertas, Yeison Andres (Frontiers in Blockchain, 2025)
Digital citizenship in Colombia is a strategic priority to modernize public services through secure, transparent, and citizen-centered interactions. The national model combines Digital Authentication, the Digital Citizen Folder, a Digital Wallet, and Digital Signature under the regulatory framework led by the Ministry of ICT. Yet adoption has been limited by mistrust, especially concerns about information security, identity theft, and limited control over personal data. This article is a narrative Mini-review that offers a curated synthesis of recent literature on blockchain for digital identity, authentication, and citizen data management, drawing on representative studies indexed in Scopus, ScienceDirect, and Google Scholar. Prior work suggests that distributed ledgers can enhance immutability, auditability, and data sovereignty, and that Self-Sovereign Identity (SSI) with verifiable credentials and decentralized identifiers can enable selective disclosure and stronger user control. However, persistent challenges include scalability and cost, governance and interoperability with legacy systems, and regulatory alignment, which temper expectations. Taken together, the literature indicates that blockchain can be a viable complement to Colombia’s digital government ecosystem when implemented through permissioned or hybrid designs, aligned with open standards and embedded in robust legal and institutional frameworks. Under these conditions, blockchain-based approaches may help rebuild trust and foster broader adoption of citizen-oriented digital services.